Genetic Cell-Surface Modification for Optimized Foam Fractionation - Blesken, Christian C.; Bator, Isabel; Eberlein, Christian; Heipieper, Hermann J.; Tiso, Till; Blank, Lars M. (Frontiers in Bioengineering and Biotechnology, 2020)
Rhamnolipids are among the glycolipids that have been investigated intensively in the last decades, mostly produced by the facultative pathogen Pseudomonas aeruginosa using plant oils as carbon source and antifoam agent. Simplification of downstream processing is envisaged using hydrophilic carbon sources, such as glucose, employing recombinant non-pathogenic Pseudomonas putida KT2440 for rhamnolipid or 3-(3-hydroxyalkanoyloxy)alkanoic acid (HAA, i.e., rhamnolipid precursors) production. However, during scale-up of the cultivation from shake flask to bioreactor, excessive foam formation hinders the use of standard fermentation protocols. In this study, the foam was guided from the reactor to a foam fractionation column to separate biosurfactants from medium and bacterial cells. Applying this integrated unit operation, the space-time yield (STY) for rhamnolipid synthesis could be increased by a factor of 2.8 (STY = 0.17 gRL/L∙h) compared to the production in shake flasks. The accumulation of bacteria at the gas-liquid interface of the foam resulted in removal of whole-cell biocatalyst from the reactor with the strong consequence of reduced rhamnolipid production. To diminish the accumulation of bacteria at the gas-liquid interface, we deleted genes encoding cell-surface structures, focusing on hydrophobic proteins present on P. putida KT2440. Strains lacking, e.g., the flagellum, fimbriae, exopolysaccharides, and specific surface proteins, were tested for cell surface hydrophobicity and foam adsorption. Without flagellum or the large adhesion protein F (LapF), foam enrichment of these modified P. putida KT2440 was reduced by 23% and 51%, respectively. Bioreactor cultivation of the non-motile strain reduced biomass enrichment in the foam by 46% compared to the reference strain. The intensification of rhamnolipid production from hydrophilic carbon sources presented here is an example for integrated strain and process engineering. This approach will become routine in the development of whole-cell catalysts for the envisaged bioeconomy. The results are discussed in the context of the importance of interacting strain and process engineering early in the development of bioprocesses.